1994
DOI: 10.1093/treephys/14.7-8-9.659
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gas exchange characteristics during the life span of giant sequoia: implications for response to current and future concentrations of atmospheric ozone

Abstract: Native stands of giant sequoia (Sequoiadendron giganteum Bucholz) are being exposed to relatively high concentrations of atmospheric ozone produced in urban and agricultural areas upwind. The expected change in environmental conditions over the next 100 years is likely to be unprecedented in the life span (about 2,500 years) of giant sequoia. We determined changes in physiological responses of three age classes of giant sequoia (current-year, 12-, and 125-year-old) to differing concentrations of ozone, and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 7 publications
3
40
2
Order By: Relevance
“…Although the relationship between h and reference G s values is empirical at this stage, the decline in G s with increasing h agrees with ecophysiological studies at the leaf-and crown-scale level (e.g. Grulke and Miller, 1994;Schoettle, 1994;Ryan et al, 1997;Hubbard et al, 1999;Tyree, 2003). These ecophysiological studies showed a decline in stomatal and crown conductances.…”
supporting
confidence: 84%
“…Although the relationship between h and reference G s values is empirical at this stage, the decline in G s with increasing h agrees with ecophysiological studies at the leaf-and crown-scale level (e.g. Grulke and Miller, 1994;Schoettle, 1994;Ryan et al, 1997;Hubbard et al, 1999;Tyree, 2003). These ecophysiological studies showed a decline in stomatal and crown conductances.…”
supporting
confidence: 84%
“…Most comparisons of seedlings vs. mature trees showed greater ozone sensitivity in seedlings, including red spruce (Rebbeck and Jensen 1993), sequoias (Grulke and Miller 1994), and black cherry (Fredericksen et al 1996). Greater ozone sensitivity in seedlings was attributed to larger stomatal conductances in all of these cases.…”
Section: Mechanisms Of Ozone Responsementioning
confidence: 99%
“…Jensen and Roberts (1986) also showed higher ozone sensitivity under more humid atmospheric conditions due to higher stomatal conductance. Under future conditions of higher CO 2 fertilization, it is possible that ozone damage will be reduced due to lower stomatal conductance (Grulke andMiller 1994, Fiscus et al 2005). …”
Section: Mechanisms Of Ozone Responsementioning
confidence: 99%
“…Lower conductance and ozone uptake contributed to less foliar ozone sensitivity in mature vs. seedling giant sequoia (Sequoidendron giganteum Bucholz.) (Grulke & Miller, 1994). Visible injury, stomatal conductance and leaf ozone uptake were greater in open-grown black cherry seedlings than in sun leaves of mature trees (Fredericksen et al, 1996 b).…”
Section: Seedling To Mature Treementioning
confidence: 99%